(untitled) (EAAE Annual Conference Proceedings, 2025)
A participatory approach to planning and design is no longer only the activists’ way to produce space but is today recognised as appropriate methodology to work together towards a sustainable urban development by formal decision bodies on municipal, regional, national and international level. There is however an embedded conflict in this approach in relation to pedagogy. Visionary architecture and design investigation create inevitable expectations within the involved communities. Even if most students of architecture and design want to get involved in the ’real’ world, already in their studies, this is further also complex in relation to economic aspects as well as the different timespans of course curriculums and appropriate urban development projects. This paper aims to explore possibilities and limitations of participatory involvement of architecture students feeding into already ongoing projects run by local organisations in the Global South by drawing experience from the freestanding learning programme Challenging Practice – Essentials for the Social Production of Habitat run by ASF-International, and particularly the workshop series In Situ Studio run by ASF-Sweden. These workshops reflexively investigate alternative models for affordable spatial and physical solutions together with communities, different stakeholders, and local professionals, and create cross cultural learning experiences between local and international professionals and students. Furthermore, the paper explores creative examples of participation from the organisation Dansbana! (run by the architects Anna Pang, Anna Fridolin and Teres Selberg), to visualise a playful participatory design process while creating public spaces for dance with young girls as focus group. Embracing the notion that we as architects, are “as experts, a special kind of people, and accept also, that everyone out there, are also a special kind of expert”1. This attitude leaves architects and designers, working with participatory methods, with the ability to stay creative and dare to propose spatial outcomes unimaginable for the participants, something that this paper states, is also most fruitful for the involved communities and their built public environment.